Development of Future Law Specialists Professional Growth Through International Internships - Ляшенко, Ірина Володимирівна (Educological discourse, 2014)
The article reveals the ways of development of a law successful future specialist through the international trainings. The attention is paid to the motivation component of the professional development, training component and international mobility as a significant motivational factor of professional growth.